The missing point in CAFTA - José Antonio Reyes (Inter-American Development Bank, Research Department, 2007)
Ports are a crucial element in any Free Trade Agreement because of their role in moving goods. Unfortunately, the port situation in Central America was not considered during Free Trade Agreement negotiations with the United States (CAFTA). Although CAFTA is intended to provide benefits for exporters and importers, these benefits will not be fully realized due to the region's high port costs. These high costs, along with concerns regarding infrastructure, security, efficiency, and productivity, can diminish CAFTA's potential benefits. Central America must therefore enact legal reforms to privatize port operations, as the private sector possesses the resources necessary to invest in those ports and make them competitive.
Keywords: 330